Sosialisasi Penerapan Iptek Sistem Kasir On-Premise untuk Meningkatkan Efisiensi Transaksi dan Akurasi Data pada Toko Ibu Siti - Nugraha, Muhamad Fahmi; Moh. Abdul Aziz; Sofia Dewi (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2026)
The use of digital technology in MSMEs is still uneven, especially in small businesses that still rely on manual recording such as at Toko Ibu Siti, so that the transaction process becomes slow and there is a risk of errors. This activity aims to implement an on-premise-based cashier system that is in accordance with business conditions and helps improve user understanding in operating it. The method used is qualitative descriptive with a participatory approach through observation, interviews, and questionnaires. The results of the activity show that there are quite clear changes, where the transaction process becomes faster, recording is neater, and the stock of goods is easier to monitor. In addition, users can run the system independently after training, with a response that tends to be positive. The implementation of this system also encourages technology adaptation in the business environment, improves the accuracy of sales data, and enables business owners to make more effective information-based decisions. Overall, the implementation of this system is able to help improve work efficiency, reduce human error, and encourage the use of technology in small-scale businesses so as to support the sustainable growth of MSMEs.